Deformation and stability of a discontinuity-controlled rock slope at Dagangshan hydropower station using three-dimensional discontinuous deformation analysis. (June 2020) - Ma, Ke; Liu, Guoyang; Guo, Lianjun; Zhuang, Duanyang; Collins, D.S.
Abstract: The right bank slope of the Dagangshan hydropower station has undergone large deformation during excavation, which may continue to increase and cause slope instability and failure, threatening dam construction and safe operation. This study analysed the deformation and instability of this discontinuity-controlled rock slope by three-dimensional discontinuous deformation analysis (3D-DDA). A microseismic monitoring technique was adopted to capture the spatial and temporal distributions of microseismic events. The unknown geological discontinuities and the potential slip surface inside the slope were determined. By combining monitoring data with the geological information, the 3D-DDA model was established to analyse the 3D deformation characteristics of the slope. In addition, the slope deformation and failure under various conditions, such as over excavations, as well as various joint penetrations, joint dip directions, and friction angles were further investigated. It was found that the simulation of the critical sliding state of blocks by 3D-DDA is effective after improvement of the critical sliding model of joint contact between blocks, and the computational results showed good agreement with monitoring results. Slope deformation is caused by the accumulation of micro-crack damage in deep rock masses, and it is closely related to its internal and external conditions. Furthermore, the failure modes and mechanisms of the slope with 3D topography are presented, which may be helpful for the design of a slope reinforcement scheme.